Tropical montane birds have increased nesting success on small river islands (2015)
Predation is the most important cause of nest failure in birds, and variation in predation risk has been associated with changes in nesting behaviors such as nest-site selection. Some birds choose favorable breeding sites on oceanic or large lake islands to increase their nesting success, but we do not know whether river islands with smaller water barriers provide similar “safe” conditions that decrease predation risk. We tested this in tropical birds by comparing daily survival rates (DSR; i.e. the probability that a nest will survive a single day) and predators identified at nests among bird species that nest on river edges and islands in the Andes. We monitored natural nests of 9 species and placed 70 artificial nests of different shapes (dome, cup, and ground nests) on islands and along river edges. We found that nest survival rates were greater on islands than on river edges for both natural nests (0.989 ± 0.004 vs. 0.0975 ± 0.004) and artificial nests (0.977 ± 0.007 vs. 0.944 ± 0.012). Isol...